Contribution à l'étude de mollusques marins : Iridovirus-like et Herpèsvirus-like. Description, caractérisation biochimique, cycle de multiplication viral, diagnostic et étude épidémiologique - Renault, Tristan; Le Deuff, Rose-marie; Cochennec, Nathalie; Chollet, Bruno; Maffart, Patricia (1993)
Among the marine molluscs, Pacifie oyster, Crassostrea gigas, is actually the most reared specie in the world. Noticely in France, where it was imported between 1960 and 1970, and replaced by Portuguese oyster, Crassostrea angulata, which specie was decimated during this period because of iridoviruses. Uncontroled introductions of new species may however be hazardous. Indeed, they might be responsible for the appearance and the dissemination of new diseases of bivalve molluscs in importing country. In addition to these observations, the quasi monobreeding of Pacific oyster in France enhances the necessity to develop research concerning the diagnosis of pathologies affecting this specie, namely the diagnosis of viral diseases. Several families of viruses have been described within marine bivalve. The purposes of this work are an iridovirus and a herpesvirus-like considered as C. Gigas major potential pathologies. In a first part, different axis of work were centered round the objective to develop methods for the diagnosis of iridoviruses using a fish model. The second part of this work consisted to look for the presence of herpes-like viruses associated with larval and spat mortalities of C. gigas, and to initiate works belonging to perform diagnosis of these viral diseases L'huître creuse, Crassostrea gigas, est aujourd'hui une des espèces de mollusques marins !es plus élevées dans le monde. Notamment en France, où elle a été importée dans les années 60~70, et a remplacé l'huître portugaise, Crassostrea angulata, espèce décimée à cette époque par des iridoviroses. Cependant, il existe aujourd'hui des hypothèses impliquant le transfert d'huîtres creuses, en provenance du Japon et du Canada, dans la disparition quasi totale de C. Angulata du littoral français. Les agents viraux (iridovirus), responsables de mortalités chez l'huître portugaise pourraient avoir été transmis par l'huître creuse, C. gigas, porteur sain. Les introductions non contrôlées de nouvelles espèces ne sont donc pas sans danger, elles peuvent ...